FENOMENA PENGGUNAAN GADGET BAGI EFEKTIVITAS BELAJAR SISWA - Noverrio, Dimas Aliyanda; jumari; Masruroh, Laily (EL-Islam, 2025)
Abstract: This study discusses the phenomenon of gadget use among MAN 1 Jombang students, especially class XI and the impact on student learning effectiveness. Data obtained through field observations, direct interviews, and documentation. In this study, the impact of gadget use on the learning effectiveness of MAN 1 Jombang students includes positive and negative impacts for students. Positive impacts include accessing various educational information, as a communication tool, and one way to reduce the use of paper at school (paperless). In addition, there are negative impacts such as students not being able to manage their time, leading to addiction and health problems. Overall, this study emphasizes the importance of education on the impact of gadget use and teachers and students are expected to maximize their use in the learning process.